Jamestown Canyon virus-mediated meningoencephalitis with unusual laboratory findings. Issue 7 (1st July 2021) - Kumar, Dilpat; Hans, Anmol; Warsha, Fnu; Helmstetter, Nicholas
Abstract : Jamestown Canyon virus (JCV) is a mosquito-borne orthobunyavirus that causes an acute febrile illness, meningitis or meningoencephalitis. Human infections in the USA are rare. A 59-year-old man was admitted with fever, headache and hallucinations and required transfer to intensive care due to worsening agitation. Lumbar puncture was significant for neutrophilic pleocytosis, low glucose and high protein. Cerebral spinal fluid (CSF) bacterial cultures were negative, however, the CSF analysis via ELISA returned positive for JCV IgM. Plaque reduction neutralisation tests on a serum sample revealed IgM for JCV with titres of 1:160, which confirmed the diagnosis of JCV meningoencephalitis as the titres for other arboviruses were low. The patient improved significantly with supportive care. Our case highlights an atypical laboratory presentation of neutrophilic pleocytosis on CSF in a viral meningoencephalitis and draws attention to the potential cross-reactivity with other arboviruses.